2023
DOI: 10.1103/physrevc.107.064318
|View full text |Cite
|
Sign up to set email alerts
|

Search for the origin of wobbling motion in the A130 region: The case of Xe131

Abstract: In-beam γ -ray spectroscopy of 131 Xe was carried out to study the structure of the intruder νh 11/2 band. Excited states were populated via an α-induced fusion-evaporation reaction at E α = 38 MeV. Inspection of γ γ -coincidence data resulted in the identification of a new rotational sequence. Based on the systematics of excitation energy, assigned spin-parity, decay pattern, and the electromagnetic character of the interband I = 1 γ transitions, this sequence is proposed as the unfavored signature partner o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…Therefore, 125 Xe appears to be stabilized with a triaxial deformation of γ = 27 • (according to the TPSM calculation). Thus, this nucleus shows properties of longitudinal wobbling and this observation of wobbling in 125 Xe further strengthens the suggested correlation between wobbling motion and R E or Q 0 , as claimed by Chakraborty et al [26].…”
Section: Data Analysis and Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, 125 Xe appears to be stabilized with a triaxial deformation of γ = 27 • (according to the TPSM calculation). Thus, this nucleus shows properties of longitudinal wobbling and this observation of wobbling in 125 Xe further strengthens the suggested correlation between wobbling motion and R E or Q 0 , as claimed by Chakraborty et al [26].…”
Section: Data Analysis and Resultssupporting
confidence: 89%
“…The transverse wobbling charac-034301-2 teristics proposed in some of the nuclei are debatable [25]. In a recent publication on 131 Xe by Chakraborty et al, [26], the authors concluded that odd-A nuclei, where a wobbling band has been observed, are mostly surrounded by two even-even nuclei with R E 2.3 and Q 0 2.6 b (where…”
Section: Introductionmentioning
confidence: 99%